2010
DOI: 10.1590/s1413-81232010000600014
|View full text |Cite
|
Sign up to set email alerts
|

Violência contra a pessoa idosa: análise de aspectos da atenção de saúde mental em cinco capitais brasileiras

Abstract: Violência contra a pessoa idosa: análise de aspectos da atenção de saúde mental em cinco capitais brasileirasViolence against the elderly: analysis of aspects of mental health care in five Brazilian citiesResumo Trata-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
2
0
15
Order By: Relevance
“…If we (mental health workers) are not together (psychological) attention is not given. These findings match previous studies (Valadares and Souza, 2010) that showed restrictions for those with mental disorders in receiving attention from the health services in general.…”
Section: What Is This Network?supporting
confidence: 92%
“…If we (mental health workers) are not together (psychological) attention is not given. These findings match previous studies (Valadares and Souza, 2010) that showed restrictions for those with mental disorders in receiving attention from the health services in general.…”
Section: What Is This Network?supporting
confidence: 92%
“…Diante das distinções entre classes sociais, preconceito contra o envelhecer e o culto à juventude, há um cenário que propicia a invisibilidade da violência, não havendo no Brasil, ainda, dados que permitam de fato conhecer a predominância deste tipo de violência (Apratto e Morais, 2010). Reconhecimento da violência intrafamiliar contra idosos pela equipe da estratégia saúde da família (Shimbo, Labronici, & Mantovani, 2011) Revisão sistemática da produção acadêmica brasileira sobre causas externas e violências contra a pessoa idosa (Minayo,Souza, & Paula, 2010) Percepções de gestores e profissionais de saúde sobre a atenção aos idosos vitimas de violências no município do Rio de Janeiro (Cavalcanti & Souza, 2010) Atendimento pré-hospitalar ao idoso vitima de violência em cinco capitais brasileiras (Deslandes & Souza, 2010) Analise psicossocial da violência contra idosos (Araújo & Lobo Filho, 2009) A violência domestica contra idosos nas áreas de abrangência do Programa Saúde da Família de Niterói (Apratto, 2010) Assistência a saúde dos idosos vitimas de acidentes e violência: uma analise da rede de serviços SUS no Recife (Lima et al, 2010) Avaliação construtivista, sob uma abordagem integradora e intersetorial, das ações do Projeto Disque Idoso em Sobral (Freitas & Teófilo, 2010) Violência contra a pessoa idosa: analise de aspectos da atenção de saúde mental em cinco capitais brasileiras (Valadares & Souza, 2010) Atendimento de reabilitação à pessoa idosa vítima de acidentes e violência em distintas regiões do Brasil (Ribeiro & Barter, 2009) Título do artigo/ Autor/ Ano Objetivo da publicação Dificuldades enfrentadas Formas de enfrentamento * alannademedeiros@hotmail.com * * ilanapaiva@hotmail.com ***tltorres2@yahoo.com.br LIBERABIT: Lima (Perú) 22 (2): [185][186][187][188][189][190][191][192][193][194][195][196]2016 No resgate histórico da questão sociofamiliar, a literatura apontou que apesar dos avanços atuais, nem sempre a violência contra o idoso foi compromisso de todos. Inicialmente era tratada como questão familiar, até o fomento às políticas públicas, no século XX, o que culminou com os direitos e amparos legais.…”
Section: Resultsunclassified
“…31 This study also reveals that lethality was predominant among 80 year-old or older women, which may also be related to associated comorbidities present at this age. 31 Violence against the elderly more frequently occurs at home, [32][33] which may be caused by a sense of devaluation of seniors and when different generations live together. When various family members live in the same home, conflict of generation and values may arise and be worsened by the senior's vulnerability or frailty, 34 and also exacerbated by relationships in which financial dependence, weak affective bonds, or the presence of any mental or psychiatric disorder exist, among others.…”
Section: Discussionmentioning
confidence: 99%